Overreporting of the disc herniation in lumbar spine MRI scans performed for patients with spondylolisthesis. (March 2021) - Semaan, Hassan; Curnutte, Bryan; Cooper, Maxwell; Obri, Joud; Elsamaloty, Mazzin; Obri, Tawfik; Elgafy, Hossein
Background: Spondylolisthesis is often misdiagnosed on magnetic resonance imaging (MRI) as the slip may reduce to a normal alignment when the patient lies supine. Often, disc herniation is reported at the level of spondylolisthesis. Purpose: To determine the incidence rates of disc herniation at the level of spondylolisthesis. Material and Methods: This is a retrospective study included 258 consecutive patients with spondylolisthesis who had lumbar spine MRI. The archived reports were collectively put in Group 1. A musculoskeletal radiologist and a spine surgeon reviewed the imaging studies together. Their readings were referred to as Group 2. The findings of both groups were compared to evaluate whether disc herniation was overreported. Results: Group 1 reported findings of true disc herniation in 112 (41.6%) cases and pseudo disc herniation or no findings of disc herniation at the level of spondylolisthesis in 157 (58.4%) cases. Group 2 reported findings of a true disc herniation in 25 (9.3%) cases and pseudo disc herniation or no findings of disc herniation in the remaining 244 (90.7%) cases. There was a statistically significant difference in the reporting rates between these two groups ( P < 0.02). The most overreported finding was the disc bulging ( P < 0.01). Conclusion: The current study showed overreporting of disc herniation in lumbar spine MRI scans performed for patients with established spondylolisthesis. The majority of disc pathology at the level of spondylolisthesis are pseudo disc rather than a true disc herniation. An accurate diagnosis is vital in planning surgical intervention.